Order of swans [large type] - Deveraux, Jude (Deveraux, Jude. Blue Swan duology, 2025)
"To Kaley Arens, a PhD student and expert in folklore, fairy stories have always had a power and an allure beyond mere entertainment. It's only when Kaley accompanies her lifelong friend Jobi on a visit to his home that she realizes how much she still has to learn. Bellis isn't the remote island that she believed it to be. It's another world--a stunningly beautiful and seductive one, with its own royalty, its own rules, and inhabitants who breathe life into the tales she was taught were fiction. Kaley's presence is no simple holiday. She has a mysterious connection with Jobi and with Bellis, and abilities that may help determine this world's fate. Tasked with locating a lost prince, Kaley and her companions--the enigmatic Tanek, a member of the Order of Swans, and Sojee, Kaley's colossal bodyguard--journey through a land both thrilling and terrifying, where the uncanny and the familiar go hand in hand. But in fairy tales, heroes and villains are easy to discern. Here, nothing is quite as it seems. And though Kaley is discovering that she can change the outcome of the fairy tales she knows so well, her own story is unfolding in ways impossible to predict, with a destiny she could never have foretold..." --